2022
DOI: 10.1155/2022/1861130
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the Minor Season Rainfall over Southern Ghana (1981–2018)

Abstract: The monitoring of rainfall variability over recent decades has become a necessity due to its devastating effects such as floods and droughts, which render humans vulnerable across different parts of the West African region. The current study seeks to provide a good understanding of variability within the minor rainfall season over southern Ghana by employing statistical tools to quantify variability in rainfall. Daily rainfall data from 1981 to 2018 for seventeen (17) synoptic weather stations across southern … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…According to [65], the variability of the major season is strongly affected by atmospheric moisture that may result in upward humidity trends over the minor period. A recent study by [66] determined a growing rainfall tendency during the minor cycle that agrees with the Mann-Kendall trend results. Also, the greening of the rain forest causes higher surface moisture which most likely enhances the amount of precipitation.…”
Section: Climate Variabilitysupporting
confidence: 82%
“…According to [65], the variability of the major season is strongly affected by atmospheric moisture that may result in upward humidity trends over the minor period. A recent study by [66] determined a growing rainfall tendency during the minor cycle that agrees with the Mann-Kendall trend results. Also, the greening of the rain forest causes higher surface moisture which most likely enhances the amount of precipitation.…”
Section: Climate Variabilitysupporting
confidence: 82%
“…In June, the average monthly rainfall is about 175 mm and the highest daily rainfall ever recorded since 2000 was 212.8 mm received on 3 June 2015 [47]. However, there have been growing concerns in the media over the last decade about the increasing occurrence of extreme rainfall events in the minor season (see [48]). This means that floods due to these extreme rainfall events are increasing in frequency and severity in Accra and hence, In June, the average monthly rainfall is about 175 mm and the highest daily rainfall ever recorded since 2000 was 212.8 mm received on 3 June 2015 [47].…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…This means that floods due to these extreme rainfall events are increasing in frequency and severity in Accra and hence, In June, the average monthly rainfall is about 175 mm and the highest daily rainfall ever recorded since 2000 was 212.8 mm received on 3 June 2015 [47]. However, there have been growing concerns in the media over the last decade about the increasing occurrence of extreme rainfall events in the minor season (see [48]). This means that floods due to these extreme rainfall events are increasing in frequency and severity in Accra and hence, exacerbating the exposure of infrastructure and human livelihoods to flooding [49] modelled flooding within the Greater Accra Metropolitan Area (GAMA) and identified these neighbourhoods as some of the flood bluespots in Accra.…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…Again, Atiah et al [36] found a significant decrease in wet extreme indices over Volta Lake and an increase in wet extreme indices over northern Ghana. In addition, Braimah et al [37] found no significant trends in the number of very wet and extremely wet days in southern Ghana. Variability in temperature and rainfall, as well as an increase in the frequency of extreme weather or climate events, have devastating effects on society, especially in West Africa [38,39] and Ghana, where most of the population relies on rain-fed agriculture [40,41].…”
Section: Introductionmentioning
confidence: 95%